Stability of solutions of Caputo fractional stochastic differential equations - Xiao, Guanli; Wang, JinRong (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we study the stability of Caputo-type fractional stochastic differential equations. Stochastic stability and stochastic asymptotical stability are shown by stopping time technique. Almost surly exponential stability and pth moment exponentially stability are derived by a new established Itô’s formula of Caputo version. Numerical examples are given to illustrate the main results.
Keywords: Caputo fractional derivative; stochastic differential equations; stability